The crystal structure of 2-(3,6-di-tert-butyl-1,8-diiodo-9H-carbazol-9-yl)acetonitrile, C22H24I2N2 - Tang Lin-Li; Zeng Fei (Zeitschrift für Kristallographie - New Crystal Structures)
C22H24I2N2, orthorhombic, Pbca (no. 33), a = 21.069(4) Å, b = 8.7963(17) Å, c = 23.757(5) Å, V = 4402.8(15) Å3, Z = 8, Rgt(F) = 0.0530, wRref(F2) = 0.1569, T = 296(2) K.